Managing the Risk of Living: Life Imprisonment, the Medical Gaze and the Construction of the Paroled Body - Dagan, Netanel (The British journal of criminology, 2024)
Drawing on Israeli life-sentence parole hearings, we argue that release decisions are centred on the body, not the soul. The board employs a ‘medical gaze’ that dissects the paroled body by magnifying the applicant’s dying body and narrowing the gaze to evaluate the days left to live. A new risk emerges: the risk of living upon release rather than dying. The board is ambivalent when managing this risk: the body is treated with suspicion, the applicant is criticized for their bodily state and risk and populist discourses are recalled to back parole decisions. Contrary to the conventional wisdom that portrays parole as focussing on rehabilitation and risk, the construction of the paroled body to manage the risk of living amounts to denying any moral worth or possibility of personal growth.